Field Observations During the Eighth Microwave Water and Energy Balance Experiment (MicroWEX-8): from June 16 through August 24, 2009 - Tara Bongiovanni; Heather Enos; Alejandro Monsivais-Huertero; Blaire Colvin; Karthik Nagarajan; Jasmeet Judge; Pang-Wei Liu; Juan Fernandez-Diaz; Roger De Roo; Yuriy Goykhman; Xueyang Duan; Daniel Preston; et al. (EDIS)
In order to really accurately predict weather and near-term climate, it is necessary to take into consideration soil moisture in the top meter of soil: it governs moisture and energy fluxes at the land-atmosphere interface, and it plays a significant role in partitioning of the precipitation into runoff and infiltration. This 68-page report presents the observations of an experiment using remotely sensed microwave observations with a view towards incorporating the findings into the models used to estimate energy and moisture fluxes and improve root zone soil moisture estimates. Written by Tara Bongiovanni, Heather Enos, Alejandro Monsivais-Huertero, Blaire Colvin, Karthik Nagarajan, Jasmeet Judge, Pang-Wei Liu, Juan Fernandez-Diaz, Roger De Roo, Yuriy Goykhman, Xueyang Duan, Daniel Preston, Ramesh Shrestha, Clint Slatton, Mahta Moghaddam, and Anthony England, and published by the UF Department of Agricultural and Biological Engineering, August 2011.